Bio-based composites for high-performance materials : from strategy to industrial application - Smitthipong, Wirasak; Chollakup, Rungsima; Nardin, Michel, Ph. D. (Boca Raton : CRC Press, Taylor & Francis, 2015)
'This timely text integrates disciplines such as materials science, polymer chemistry, plant science, chemical engineering, and nanotechnology to provide comprehensive coverage of the state of the art in bio-based composite materials, as well as their biological feedstocks, basic design principles, properties, industrial applications, environmental friendliness, and life cycles. It presents a strategic and policy-oriented view of bio-based composites, addressing the competing needs for plants as food versus plants as manufacturing feedstocks, while considering the costs of retrofitting existing chemical production plants for bio-based composite manufacture.'--
Includes bibliographical references and index.
Keywords: Composite materials; Polymeric composites; Fibrous composites; Biomass chemicals